القيم التربوية في فكر البشير الإبراهيمي - حامد، أمال (جامعة الوادي university of Eloued, 2019)
résumé This study purpose identify the educational values which are included in the book of the traces of Imam Muhammad al-Bashir Al-Ibrahimi, Part I. The main question is: - What are the most important educational values in the thinking of Al-Bashir IBrahimi? The analytical descriptive approach was based on the content analysis tool (the unit of analysis was the unity of the idea). The validity of the tool was verified. The student extracted 12 values divided into three fields: religious, social, national. The sample was selected in an intentional way, represented by the book of the traces of Imam Muhammad al-Bashir al-Ibrahimi Part I .The student used the repetitions and percentages in the quantitative analysis process. The study showed the following results: The Book of the effects of Imam Muhammad al-Bashir Al-Ibrahimi Part I included the following educational values: values related to the religious sphere, values related to the social sphere, values related to the national sphere. The Book of the Antiquities of Imam Muhammad Al-Bashir Al-Ibrahimi Part I focused on the values of the religious fields represented in: pride in the Islamic religion, memorizing the Qur'an, acquiring individual and collective behavior that corresponds to the noble values of Islam, religious duties.
دراسة وصفية تحليلية لكتاب «آثار الإمام محمد البشير الابراهيمي» الجزء الأول
مذكرة ماستر في علم الإجتماع تخصص علم إجتماع التربية
Keywords: القيم التربوية، البشير الإبراهيمي; Bashir Brahimi, valeurs éducatives; Al-Bashir Al-Ibrahimi, educational values